Green Energy in the CEE-4: Milestones and Achievements - Andreea – Emanuela DRĂGOI; Paul CALANTER; Cornelia NEAGU (Communications of International Proceedings, 2021)
Given the current European legal framework and the Green Deal implications for all the EU Member States, this paper proposes a comparative analysis regarding the progress of renewable energy sources (RES) in the CEE-4 countries (Czech Republic, Hungary, Poland and Romania). Our analysis aims to highlight (using the latest European statistics) the progress on four main indicators: share of RES using in total energy, share of RES in total electricity consumption, share of RES for heating and cooling and share of RES for transport. We will also present, based on the literature in the field, how the current Green Deal may impact RES future development among CEE-4.  Our main finding will underline Romania’s progress regarding RES aiming to explain its success among CEE-4 through a SWOT analysis of policies and support schemes, while highlighting the significant differences compared with other CEE-4 countries. The concluding part of our article shows the main opportunities and challenges in the field, while debating the possible future impact of the current COVID-19 crisis on RES in CEE-4.
Keywords: Renewable Energy Sources; CEE-4; Green Deal; RES Support Schemes; COVID-19 Crisis.